2018
DOI: 10.3390/min8080312
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Primary Copper Sulfide Ore in Chloride-Ferrous Media

Abstract: Copper extraction from primary copper sulfide ore from a typical porphyry copper deposit from Antofagasta, Chile, was investigated after leaching with a chloride-ferrous media at two temperatures. The study focused on whether this chemical leaching system could be applied at an industrial scale. Leaching tests were conducted in columns loaded with approximately 50 kg of agglomerated ore; the ore was first cured for 14 days and then leached for 90 days. The highest copper extraction, 50.23%, was achieved at 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…This agrees with the observations of Miki et al [13] who reported that the copper recovery from synthetic covellite increased marginally with an increasing chloride concentration in the range of 7-90 g/L. extensive research reported for copper ores with chloride, even for the leaching of concentrates and primary sulfides copper ores [26,[30][31][32][33][34][35].…”
Section: Effect Of Strong Chloride Mediasupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with the observations of Miki et al [13] who reported that the copper recovery from synthetic covellite increased marginally with an increasing chloride concentration in the range of 7-90 g/L. extensive research reported for copper ores with chloride, even for the leaching of concentrates and primary sulfides copper ores [26,[30][31][32][33][34][35].…”
Section: Effect Of Strong Chloride Mediasupporting
confidence: 91%
“…The testing of a high chloride media similar to seawater is motivated by the scarcity of fresh water and the potential use of this resource in copper leaching [27][28][29]. There are no other studies in the literature that use a media similar to seawater for copper leaching, although there has been extensive research reported for copper ores with chloride, even for the leaching of concentrates and primary sulfides copper ores [26,[30][31][32][33][34][35].…”
Section: Effect Of Strong Chloride Mediamentioning
confidence: 99%
“…In research on the leaching of bornite done by Pesic and Olson [20], the dissolution of copper from bornite reached 26 to 28% during the first hour of the process in the presence of ferric ion, which are values greater than those obtained in this study in a chloride medium and without the initial presence of ferric ion, as shown in Figure 1. Furthermore, in the studied system, this function can be performed by the Cu 2+ /Cu + redox pair, which was formed from dissolved soluble copper [35], but it is restricted because the leaching systems require the addition of oxygen for the oxidation of the cuprous products [7,36], according to Reactions (4) and (5).…”
Section: Leaching Without Pre-treatmentmentioning
confidence: 99%
“…The leaching kinetics of chalcopyrite are slow and have remained a challenge to date. 1 The mechanisms involved in chalcopyrite dissolution have intrigued researchers, and extensive studies have been done over the past several decades, in which electrochemical studies were commonly used to study the evolution of chalcopyrite surface species because of its high sensitivity. 2,3 Present studies showed various species such as impermeable sulfur, 4 insoluble iron salts, 5 metal-deficient sulfide, 6 copper-rich polysulfide layers CuS x , 7 and nonstoichiometric sulfide Cu n−1 Fe n−1 S 2n may form during chalcopyrite dissolution.…”
Section: Introductionmentioning
confidence: 99%